AKUNTABILITAS MANAJEMEN KEUANGAN DAERAH - Ratna Agustin; Sayekti Suindyah Dwiningwarni (Nusantara Hasana Journal, 2023)
This article is entitled Regional Financial Management Accountability. The method used in this article is literature study, by reviewing several books and references related to the title of the article written. The discussion in this article contains many factors that influence Regional Financial Management Accountability. There are also other supporting factors in creating regional financial management accountability, namely the competence of the apparatus. Apparatus competence is an ability that must be possessed with adequate knowledge and skills accompanied by work experience in their field so that they can understand matters that have an impact on regional financial management accountability (Riska, 2020). If the apparatus has good competence, then the activities are carried out in compliance with the provisions so that there are no findings resulting from the BPK audit of the Regional Government Financial Statements. Competence can be increased by carrying out skills testing and routine implementation of training so that the competence and quality possessed can be increased which will affect the accountability of regional financial management. In other words, Accountability plays an important role in Regional Financial Management in order to create transparent Financial Reports. Accountability can be carried out well in Regional Financial Management if regional financial management is carried out in an orderly manner, in compliance with laws and regulations, effective, efficient, economical, transparent and responsible with due regard to the principles of justice, compliance and benefits for the wider community.